Formal, Justice‐Oriented Voice in the Nonunion Firm: Who Speaks Up and When?1. Issue 2 (April 2015) - Klaas, Brian; Ward, Anna‐Katherine
<x xml:space="preserve">Abstract</x> Employee willingness to exercise workplace voice has been the subject of much recent research. However, very different types of voice are observed within the workplace, with some forms of voice receiving limited scholarly attention. In particular, limited attention has been given to the determinants of formal, justice‐oriented voice within a nonunion context. Using a policy‐capturing design, we examine factors that affect decisions to use formal, justice‐oriented voice among 498 nonunion employees who had access to the same appeal procedure. The results suggest that this type of voice is affected by perceptions regarding immunity from negative managerial reactions to voice and also by factors associated with the utility of voice (e.g., the social power of those involved in the appeal and the evidence available to support the appeal). The results further suggest that perceived immunity moderates the impact of the social power of those involved in the appeal and the evidence available.